ANALISIS YURIDIS KEJAHATAN TERHADAP IDEOLOGI NEGARA BERDASARKAN UNDANG – UNDANG NO 27 TAHUN 1999 - Ikramul Fajri; Erdianto Erdianto; Davit Rahmadhan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The This research is motivated by one problem, namely Ideological offensesregulated in Law Number 22 of 1997 concerning Amendments to the Criminal CodeRelating to Crimes Against State Security (hereinafter referred to as Articles 107a toArticle 107f of the Criminal Code). The existence of these provisions as a result of thedark history of the Indonesian people against the PKI.The purpose of this research is to analyze the Implementation of Law Number 27of 1999 concerning Amendments to the Criminal Code relating to Crimes Against StateSecurity. Law Number 27/1999 explicitly regulates the prohibition of spreading leftistideology by inserting six new articles in Chapter I — concerning Crimes Against StateSecurity — of the Criminal Code, namely between Article 107 and Article 108, which aremade into Article 107 a, Article 107 b, Article 107 c, Article 107 d, Article 107 e, andArticle 107 f .From the results of the research conducted, it shows that the implementation ofLaw Number 27 of 1999 basically regulates two types of crimes, namely: crimes relatedto replacing Pancasila as the state ideology and crimes of sabotage, especially sabotage ofmilitary facilities and infrastructure and sabotage of distribution or procurement staple.Keywords: CRIMES AGAINST STATE IDEOLOGY